Experiences sharing and training on conservation agriculture and sustainable mechanization in Kenya - Mutai, Weldone; Mkomwa, Saidi; Kuria, Peter; Ooro, Patrick; Rogoncho, Linet M; Langat, Brolline; Waswa, Boaz (2024)
Adoption of Conservation Agriculture (CA) requires a mindset change, change that is often gradual and which comes from sustained exposure to CA and its benefits. A training and experiences sharing event was organized under the CGIAR Initiative Diversification in East and Southern Africa, referred to as Ukama Ustawi, to enhance participants’ knowledge and sensitize them on best bet practices of CA and appropriate mechanization. The training held at KALRO Njoro in Nakuru was attended by 29 participants who included lead farmers and UU project field support technicians and the project partners (from KALRO Njoro, CIAT, ACT, ADS Central Riff and World Renew). The training also included a field visit to large scale CA farmer, Madrugada farm, and the small-scale farmer, Mrs. Pauline Mogambi - APEA farm. The field practicals were quite impressive and boosted the understanding of participants on CA and its importance and built great confidence in scaling CA practices in Nakuru County.